Antioxidant Activity and Consumer Acceptance Level of Sargassum hytsrix Seaweed Tea Enriched with Lemongrass Powder - Erina Meta; Husni Amir (BIO Web of Conferences)
Sargassum hystrix contains high antioxidant activity, so it has the potential to be a good raw material for product development such as seaweed tea. However it still has a drawback, namely the presence of a fishy aroma that is not liked by the consumers. Therefore to balance the aroma, this study aims to determine the effect of adding lemongrass powder on antioxidant activity and consumer acceptance of S. hystrix seaweed tea. The treatments used in this study were variations in the addition of lemongrass powder of 0, 10, 15, 20, and 25%. The tests carried out included water content, total phenol content, antioxidant activity (2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) methods), hedonic test, and quantitative descriptive analysis (QDA). The results showed that the addition of lemongrass powder affected total phenol content, antioxidant activity, consumer acceptance level, and aroma perception in the QDA test. The best performance was the addition of 20% lemongrass powder with the characteristics of water content of 6.42 ± 0.13%, total phenol content of 8.07 ± 0.2 mg GAE/g, antioxidant activity (DPPH method 84.17 ± 2.19%, FRAP method 22.24 ± 0.56 mM/g). The highest overall hedonic value was obtained by adding 20% lemongrass powder.